Multi-biological functions of intermedin in diseases - Yang, Zhi; Li, Hongchun; Wu, Pengfei; Li, Qingyan; Yu, ChunYan; Wang, Denian; Li, Weimin (Frontiers in Physiology, 2023)
Intermedin (IMD) is a member of the calcitonin gene-related peptide (CGRP)/calcitonin (CT) superfamily, and it is expressed extensively throughout the body. The typical receptors for IMD are complexes composed of calcitonin receptor-like receptor (CLR) and receptor activity-modifying protein (RAMP), which leads to a biased activation towards Gαs. As a diagnostic and prognostic biomarker, IMD regulates the initiation and metastasis of multiple tumors. Additionally, IMD functions as a proangiogenic factor that can restrain excessive vascular budding and facilitate the expansion of blood vessel lumen, ultimately resulting in the fusion of blood vessels. IMD has protective roles in various diseases, including ischemia-reperfusion injury, metabolic disease, cardiovascular diseases and inflammatory diseases. This review systematically elucidates IMD’s expression, structure, related receptors and signal pathway, as well as its comprehensive functions in the context of acute kidney injury, obesity, diabetes, heart failure and sepsis. However, the precise formation process of IMD short peptides in vivo and their downstream signaling pathway have not been fully elucidated yet. Further in-depth studies are need to translate IMD research into clinical applications.